UNDERSTANDING ISLAMIC SYMBOLS IN RAMADHAN SPECIAL ADVERTISEMENTS: A DISCOURSE ANALYSIS - Ais Rifka Oktavia; Nadya Amalia Nasution (Universitas Islam Negeri Mataram, 2023)
Verbal symbols use both spoken and written language. In contrast, non-verbal symbols can include pictures, clothing, smiling faces, and movements and strategies that advertisers use to manipulate and influence their customers. This research uses qualitative methods, while this type uses Teun Van Dijk's media representation approach and discourse analysis. The discourse embedded in television advertising has a significant influence on its audience. The results show that advertisers promote their products and highlight people's cultural and religious values. This emphasis on Islamic rules is reflected in Muslim women's clothing styles, lifestyles, and how TV advertising has shaped ideology in social practices in Indonesia.